The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1103/physrevlett.109.126804
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Hall to Charge-Density-Wave Phase Transitions inABC-Trilayer Graphene

Abstract: ABC-stacked trilayer graphene's chiral band structure results in three (n = 0, 1, 2) Landau level orbitals with zero kinetic energy. This unique feature has important consequences on the interaction driven states of the 12-fold degenerate (including spin and valley) N = 0 Landau level. In particular, at many filling factors νT = ±5, ±4, ±2, ±1 a quantum phase transition from a quantum Hall liquid state to a triangular charge density wave occurs as a function of the single-particle induced LL orbital splitting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 28 publications
0
28
0
1
Order By: Relevance
“…[5][6][7][8] The subsequent filling factors are related to the lifting of the degeneracy of the lowest Landau level: first ν = 3 and at higher fields ν = 1, 2, and 5, a sequence which is in agreement with Hund's rules of ABC-TLG. 28,29 However, filling factor ν = 4 is also observed experimentally in this sequence whereas it is not predicted by Hund's rules for ABC-TLG. We attributed its appearance to a layer asymmetry caused by an external electric field of the back gate or local inhomogeneities.…”
mentioning
confidence: 80%
“…[5][6][7][8] The subsequent filling factors are related to the lifting of the degeneracy of the lowest Landau level: first ν = 3 and at higher fields ν = 1, 2, and 5, a sequence which is in agreement with Hund's rules of ABC-TLG. 28,29 However, filling factor ν = 4 is also observed experimentally in this sequence whereas it is not predicted by Hund's rules for ABC-TLG. We attributed its appearance to a layer asymmetry caused by an external electric field of the back gate or local inhomogeneities.…”
mentioning
confidence: 80%
“…At temperatures below 5K, transport experiments found gap openings of about 2-3 meV [7][8][9] . For trilayer graphene the stacking order is crucial for the electronic properties [20][21][22][23][24][25][26][27][28][29] . In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…23 It has been suggested that the differences in the quantum Hall effect between ABC and ABA stacking might be used to identify the stacking order of high-quality trilayer samples. 24,25 By using infrared absorption spectroscopy, it has been shown that the optical conductivity spectra for ABC-and ABA-stacked graphene differs considerably. 26 These optical properties have been calculated and reproduced in the framework of a tight-binding model.…”
mentioning
confidence: 99%